An experimental study to compare the grip of classical style roller skis with on-snow skiing - Ainegren, M.; Carlsson, P.; Tinnsten, M. (Sports Engineering, 2013)
Cross-country skiers use roller skis for their snow-free training with the aim of imitating skiing on snow. Also, exercise laboratories evaluate the biomechanics and physiology of cross-country skiing using roller skis on a treadmill. The roller skis on the market that are constructed for use in the classical style are equipped with a front and a back wheel, one of which has a ratchet to enable it to grip the surface when diagonal striding and kick double poling (static friction). The aim of this study was to investigate static friction coefficients (uS) of ratcheted wheel roller skis, and compare the results to the uS reported from skiing on snow with grip-waxed cross-country skis. Also, a new type of roller ski with a camber and adjustable grip function was evaluated. The results showed that ratcheted wheel roller skis, on a treadmill rubber mat and on dry and wet asphalt surfaces, reached uS values that were five to eight times greater than the values reported from on-snow skiing with grip-waxed cross-country skis. For the roller skis with a camber and adjustable grip function, the uS could be varied from no grip at all up to the level of the tested ratcheted wheel roller skis.